2013
DOI: 10.1002/jgra.50239
|View full text |Cite
|
Sign up to set email alerts
|

Links between the plasmapause and the radiation belt boundaries as observed by the instruments CIS, RAPID, and WHISPER onboard Cluster

Abstract: [1] In the present work, we study the relations between the position of the plasmapause and the position of the radiation belt boundaries. The Cluster mission offers the exceptional opportunity to analyze those different regions of the inner magnetosphere with identical sensors on multiple spacecraft. We compare the positions of the radiation belt edges deduced from CIS (Cluster Ion Spectrometry) observations (electrons with energy > 2 MeV) with the positions of the plasmapause derived from WHISPER (Waves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
4
22
0
Order By: Relevance
“…We notice that Darrouzet et al [2013] here, we find that the difference between the same WHISPER observations and the predictions of our model fit functions is similarly substantial. Comparison between the WHISPER observations on Cluster and those on THEMIS used in the present work may be worthwhile to do in a future work.…”
Section: Construction Of Best Fit Models and Comparison With Existingsupporting
confidence: 73%
See 1 more Smart Citation
“…We notice that Darrouzet et al [2013] here, we find that the difference between the same WHISPER observations and the predictions of our model fit functions is similarly substantial. Comparison between the WHISPER observations on Cluster and those on THEMIS used in the present work may be worthwhile to do in a future work.…”
Section: Construction Of Best Fit Models and Comparison With Existingsupporting
confidence: 73%
“…We notice that Darrouzet et al [] determined the plasmapause locations based on the observations by the WHISPER instrument onboard Cluster for a 2 year interval from April 2007. They compared the observed plasmapause locations with the predictions of the Dst ‐ and Kp ‐dependent model fit functions of O'Brien and Moldwin [] and those of the Kp ‐dependent model fit function of Carpenter and Anderson [].…”
Section: Resultsmentioning
confidence: 99%
“…Using simultaneous observations of the Cluster instruments RAPID, CIS and WHISPER, Pierrard and Benck (2012) and Darrouzet et al (2013) showed also observed links between the position of the plasmapause and the locations of the electron radiation belts boundaries for different energies. Cluster spacecraft continue to provide observations that can be compared with EPT.…”
Section: Discussion Conclusion and Perspectivesmentioning
confidence: 82%
“…The ring current arises from the azimuthal motion of trapped particles in the inner magnetosphere and roughly straddles the plasmapause (Darrouzet et al 2013). The main contributors to the current density are 1-100 keV ions.…”
Section: Introductionmentioning
confidence: 99%